TEACHER TRAINING IN THE CONTEXT OF INCLUSIVE EDUCATION: METHODOLOGICAL DIMENSION - Dzerviniks, Janis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
In accordance with the current pedagogical principles, the view is emphasized that education should be individual-oriented, socially responsible, and inclusive. Inclusive education is focused on providing education for all children, regardless of their needs. The article deals with the emphases of inclusive education in the teacher training; evaluation of the study program "Teacher" is carried out on the basis of the criteria developed. The explored prior experience is a basis to improve methodology, content, and organization of the pedagogical study programs. It is essential that the prospective teachers would receive qualitative methodological support for the implementation of inclusive education.